Agreement on the establishment of the International Livestock Research Institute - International Livestock Research Institute (International Livestock Research Institute, 1994)
Agreement on the establishment of the International Livestock Research Institute signed at Berne, Switzerland, on September 21, 1994. Agreement signed by representatives from the governments of Denmark, Ethiopia, Kenya, Sweden, Switzerland, and UNEP. Agreement is in English and contains six articles.